Oil recovery from palm oil solid wastes - Dashiny, Gopal (2009)
Many years of research have been done on extraction of residue oil from palm oil solid wastes. Decanter cake is the solid waste produced from palm oil milling company after decanting the palm oil mill effluent, while spent bleaching clay is the solid waste from palm oil refinery. Basically, this wastes still contains 30-40% of oil and this solid wastes are currently disposed directly in landfills without treatment, causing severe water and air pollution problems. Recovery of oil and the reuse of spent bleaching clay and decanter cake is the areas where great opportunity exists for cost saving in the oil processing industry. This study described the extraction of residual oils of spent bleaching earth (SBE) from palm oil refinery and also described the extraction of residue oil from palm oil milling industry. Here, two methods are used for comparison to extract the oil from decanter cake and also spent bleaching clay. There are soxhlet extraction method and also solvent decanting method. The comparison of two methods shows that soxhlet extraction can give higher yield. The optimum temperature and best duration of time to dry the decanter cake and spent bleaching clay also determined. In this case, the samples were dried at the temperatures 600C- 1100C, and the best temperature is 900C. The optimum time was determined as 12 hours. Four different solvents were used to extract the residue oil from the waste samples. The results shows that the percentage of oil extracted from Methyl ethyl ketone and acetone was high compared to hexane and petroleum ether. The iodine value was also determined to compare the quality of the oil extracted. The range of iodine value obtained was 40-80. According to PORIM analysis mean value of crude oil is 51.3.-Author-